Sport participation motives of young brazilian athletes - Dartagnan, P. G.; Netto, J. E. S. (Perceptual and Motor Skills, 2013)
Summary.—The objective of this study was to identify the motives for sport participation in a sample of young Brazilian athletes according to sex, age, and training history. A total of 1,517 participants (714 girls, 803 boys) ages 12 to 18 years were included in the study. The Portuguese version of the Participation Motivation Questionnaire was used to identify motives for sport participation. The most important motives were Skill Development and Fitness, whereas the least important were Fun and Achievement/Status. Sex, age, type of sport, onset of training, duration of training, training volume, and competitive experience significantly influenced the motives for sport participation reported by the athletes. These results will contribute to establish intervention programs designed to reduce sport dropout rates among young athletes.